Manajemen strategi pengembangan layanan digital pada bank syariah indonesia (bsi) dalam meningkatkan daya saing di era digital - Suswandi, Feri (Maliki Interdisciplinary Journal, 2025)
The advancement of digital technology has driven significant changes in the global banking industry, including the Islamic banking sector in Indonesia. Bank Syariah Indonesia (BSI), as the largest Islamic bank formed from the merger of three national Islamic banks, has become a pioneer in digital transformation to enhance competitiveness and service reach. This study aims to analyze BSI’s strategic management in developing digital services to remain competitive amid technological disruption. The research uses a descriptive qualitative approach based on secondary data from BSI’s annual reports, OJK publications, and recent academic journals. The findings indicate that BSI’s digital strategy focuses on three main aspects: innovation of digital platforms (BSI Mobile and BYOND), strengthening technological infrastructure, and integrating Sharia values into every innovation. This strategy not only improves efficiency and customer satisfaction but also reinforces BSI’s image as a modern Islamic bank that adapts to technological change.